Analisis Biaya Pemakaian Alat Berat Pada Paket Rekonstruksi Jalan Pematang Reba - Siberida (B) - Eky Permana; Rian Trikomara; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The objectives of this research are to know how much cost needed for the use of new heavy equipment and old heavy equipment at project Pematang Reba – Siberida (B) Street Reconstruction. The pavement depth planning uses component analysis from Bina Marga Method for aggregate base course and method developed by NAASRA (National Association of Australian State Road Authorities) for concrete base course. Data needed for the analysis consist of work volume details, unit cost list, unit cost analysis, equipment replacement analysis and construction drawing. Cost analysis result shows that use new heavy equiptment need Rp.8,360,450,248 and old heavy equipment need Rp.13,522,647,465 with cost saving percentage 38.17% for old heavy equipment cost.Key words: cost analysis, work grained, heavy equipment, volume.